The Association of Severe Diabetic Retinopathy With Cardiovascular Outcomes in Long-standing Type 1 Diabetes: A Longitudinal Follow-up - Pongrac Barlovic, Drazenka (Diabetes Care, 2018)
OBJECTIVE: It is well established that diabetic nephropathy increases the risk of cardiovascular disease (CVD), but how severe diabetic retinopathy (SDR) impacts this risk has yet to be determined. RESEARCH DESIGN AND METHODS: The cumulative incidence of various CVD events, including coronary heart disease (CHD), peripheral artery disease (PAD), and stroke, retrieved from registries, was evaluated in 1,683 individuals with at least a 30-year duration of type 1 diabetes drawn from the Finnish Diabetic Nephropathy Study (FinnDiane). The individuals were divided into four groups according to the presence of diabetic kidney disease (DKD) and/or SDR (+DKD/+SDR, +DKD/−SDR, −DKD/+SDR, and −DKD/−SDR) at baseline visit. Furthermore, age-specific incidences were compared with 4,016 control subjects without diabetes. SDR was defined as laser photocoagulation and DKD as estimated glomerular filtration rate <60 mL/min/1.73 m(2). RESULTS: During 12,872 person-years of follow-up, 416 incident CVD events occurred. Even in the absence of DKD, SDR increased the risk of any CVD (hazard ratio 1.46 [95% CI 1.11–1.92]; P < 0.01), after adjustment for diabetes duration, age at diabetes onset, sex, smoking, blood pressure, waist-to-hip ratio, history of hypoglycemia, and serum lipids. In particular, SDR alone was associated with the risk of PAD (1.90 [1.13–3.17]; P < 0.05) and CHD (1.50 [1.09–2.07; P < 0.05) but not with any stroke. Moreover, DKD increased the CVD risk further (2.85 [2.13–3.81]; P < 0.001). However, the risk was above that of the control subjects without diabetes also in patients without microvascular complications, until the patients reached their seventies. CONCLUSIONS: SDR alone, even without DKD, increases cardiovascular risk, particularly for PAD, independently of common cardiovascular risk factors in long-standing type 1 diabetes. More remains to be done to fully understand the link between SDR and CVD. This knowledge could help combat the enhanced cardiovascular risk beyond currently available regimens.